Albendazole sulphoxide kinetic disposition after treatment with different formulations in dogs - Dib, A. (2011)
New therapeutic strategies based on the search of alternative formulations of albendazole (ABZ) and albendazole sulphoxide (ABZSO) are under current development to optimize posology and antiparasite efficacy in dogs. In an incomplete block design, nine dogs were randomly divided into three groups (n=6). Treatments were carried out in two phases as follows. Phase I: Group I (treatment A), animals received ABZ at 25mg/kg of conventional formulation. Group II (treatment B), dogs received 25mg/kg of a modified poloxamer-ABZ formulation. Group III (treatment C), animals were treated with ABZSO in equimolar amount to ABZ doses. After 21days of wash-out period the experiment was repeated (Phase II). Blood samples were collected over 24h and subsequently analysed by high performance liquid chromatography. ABZSO and ABZSO 2 were the analytes recovered in plasma. Significant higher (P<0.001) ABZSO area under the concentration-time curve (+500%) and C max (+487%) values were obtained for the treatment C in comparison with treatments A and B. However, no statistical differences on pharmacokinetic parameters were found between formulations A and B. In conclusion, the enhanced plasma concentration profile obtained for the ABZSO formulation used in treatment C may contribute to optimize the anthelmintic control in dogs.